Lipschütz ulcers: should we rethink this? An analysis of 33 cases. (March 2016) - Vieira-Baptista, Pedro; Lima-Silva, Joana; Beires, Jorge; Martinez-de-Oliveira, José
Abstract: Objectives: To describe the presentation and characteristics of patients with Lipschütz ulcers (LU) and to evaluate the role of a standard protocol in the aetiological diagnosis. Study design: Retrospective analysis of all cases of diagnosis of LU at our Vulvar Clinic during a five-year period. Results: Of 110 women with vulvar ulcers, 33 (30.0%) had a diagnosis of LU. The mean age was 29.1 ± 15.14 years (10–79 years). Nine (27.3%) were 35 years old or more. The majority had had their sexual debut (28, 84.8%). Ten patients (30.3%) referred had at least one previous similar episode. Twenty-five (75.7%) had non-gynecological symptoms in the week before. The ulcers were located most frequently on the vestibule (19, 57.6%) and the labia minora (10, 30.3%). Isolated lesions on the left side were uncommon (3, 9.1%). Most had multiple (22, 66.7%) lesions. The mean time to full healing of the lesions was 15.6 ± 6.20 days. A microbiological possible cause was identified in 9 (27.3%) patients: CMV (3 cases), Mycoplasma pneumoniae (3 cases), EBV (2 cases) and PVB19 (1 case). The protocol did not include systematic biopsies, blood count differentials, C-reactive protein and liver enzymes, which may have lead to some missed diagnosis. Conclusions: LU can be found in women of any age, most of them sexually active. In most cases the lesions are preceded by non-gynecological symptoms and recurrence is common. Most lesions occur on the vestibule and labia minora, being rarely found isolated on the left side. Viruses seem to be the most frequent associated agents but Mycoplasma pneumoniae serology should be considered. In one case there was a possible role for PVB19. A standard protocol can effectively exclude sexually transmitted diseases and lead to a diagnosis in up to a third of cases.